Reorientasi Pembangunan Desa Di Riau - Prihatin, Panca Setyo (UIR PRESS, 2015)
According to BPS data Riau Province in 2013, Riau economy including oil and gas in the fourth quarter of 2013, as measured by the Gross Domestic Product (GDP) at constant 2000 prices grew by 1.39 percent compared to the third quarter of 2013 (q-to q), and when compared to the same quarter the previous year (fourth quarter 2012) grew 3.77 percent (y-on-y). Riau economy without oil and gas, in the fourth quarter of 2013 grew by 2.33 percent compared to the third quarter of 2013 (q-to-q), and when compared with the fourth quarter of 2012, the economy grew 6.01 percent (y-on -y). On the other hand, based on BPS data in 2013, the number of poor (people living below the poverty line) in Riau September 2013 amounted to 522.53 thousand (8.42 percent). When compared with the poor people in September 2012, amounting to 481.31 thousand (8.05 percent), the number of poor people in Riau increased by 41.22 thousand. In relative terms the increase percentage of the poor from 8.05 percent in September 2012 to 8.42 percent in September 2013. There was an increase of 0.37 percent. During the period September 2012- September 2013, poverty in rural areas is expected to grow 34.92 thousand inhabitants, while in urban areas is expected to grow by 6.3 thousand jiwa.Distribusi percentage of poor people in Riau in September 2012 in rural areas amounted to 8.94 percent , while in urban areas it was 6.68 percent. This distribution is experiencing a significant shift in September 2013, where the percentage of poor people in rural areas increased to 9.55 per cent and urban fixed by the same percentage is 6.68 percent. During the period September 2012-September 2013, the Poverty Line (PL) increased by 12.73 percent from Rp 310 603, - per capita per month in September 2012 to Rp 350 129, - per capita per month in September 2013. The role of food commodities against a much larger GK compared to the role of non-food commodities (housing, clothing, education, and health). Donations Food Poverty Line (FPL) for GK in September 2013 reached 73.72 percent. On September 2013 GKM Riau is Rp 258 100, - and Non-Food Poverty Line (NFPL) amounted to USD 92 029.